Faktor-faktor yang Mempengaruhi Tingkat Konsumsi Ikan pada Masyarakat di Kecamatan Sajad - Mar’ie , Muhammad; Saifullah, Saifullah; Istiqamah, Nur (Politeknik Negeri Sambas, 2022)
The ease of obtaining fish, especially seawater fish, makes the people of Sajad Subdistrict interested in selling fish, based on observations there are 18 to 20 people selling vegetables and seawater fish in Sajad District. The purpose of the study was to determine the level of fish consumption in the Sajad District. The method used is descriptive quantitative, sample data taken as many as 98 samples and processed using SPSS version 24. The R2 value of 0.476 means the independent variable, family (X1), the number of family members (X2), perception of fish prices (X3), tastes (X4), the level of education (X5) simultaneously affects the amount of fish consumption (Y) by 47.6%. The results of the F test show that Fcount 16,703 > Ftable 2,31, tvalue for taste = 7,606 > ttable = 1,989 and significant value 0.000 < 0.05. The respondent's taste variable (X4) is the dominant factor that affects the level of fish consumption.